Epidemiological survey of calf diarrhea related viruses in several areas of Guangdong Province - Chen, Jinping; Meng, Wenxin; Zeng, Huijuan; Wang, Jingyu; Liu, Shizhe; Jiang, Qifeng; Chen, Zihan; Ma, Zihang; Wang, Zhen; Li, Shoujun; Jia, Kun (Frontiers in Microbiology, 2024)
BToV, BEV, Bovine norovirus (BNoV), Bovine coronavirus (BCoV), Bovine rotavirus (BRV), and Bovine viral diarrhea virus (BVDV) are significant pathogens causing diarrhea in calves, characterized by their high prevalence and challenging prevention and control measures. Methods: We analyzed 295 calf diarrhea samples, amplifying the M gene from BToV-positive samples, the 5'UTR gene from BEV-positive samples, the RdRp gene from BNoV-positive samples, the VP7 gene from BRV-positive samples, the S gene from BCoV-positive samples, and the 5'UTR gene from BVDV-positive samples. Subsequent homology analysis and phylogenetic tree construction were performed. Results: The overall viral positive rate in Guangdong Province was 21.36%. Specific detection rates were as follows: Foshan City at 50.00% (18/36), Guangzhou City at 43.90% (36/82), Huizhou City at 21.21% (7/33), Yangjiang City at 2.08% (1/48), Meizhou City at 1.39% (1/72), and Heyuan City at 0.00% (0/24). The detection rates for BToV, BEV, BNoV, BCoV, BRV, and BVDV were 0.34% (1/295), 6.10% (18/295), 0.68% (2/295), 1.36% (4/295), 10.85% (32/295), and 2.03% (6/295), respectively. Notably, the highest overall virus detection rate was observed in the Guangzhou-Foshan region, with BRV and BEV showing the highest detection rates among the six viruses. This study marks the first report of BToV and BNoV in Guangdong Province. Phylogenetic analysis revealed that the BToV strain belonged to type II, sharing genetic similarities with epidemic strains from various provinces in China. The BEV strains were categorized into E and F types, with the F type being the predominant strain in Guangdong Province and exhibiting the closest genetic relationship to strains from Heilongjiang and Guangxi. The BNoV strains, along with Hebei strains, were identified as GⅢ.2 subgenotype. BCoV strains showed the highest genetic similarity to strains from Sichuan. All BRV strains were classified under the G6 subtype and had the closest genetic relationship with human rotavirus strains. BVDV strains were identified as subtype 1b, closely related to the Beijing strain. In conclusion, this study investigated the prevalence and evolutionary characteristics of diarrhea-associated viruses in calves in specific areas of Guangdong Province, providing a valuable reference for establishing effective prevention and control measures in cattle farms.